Photon-Assisted Seebeck Effect in a Quantum Dot Coupled to Majorana Zero Modes - He, Tian-Yu; Sun, Hailing; Zhou, Guofu (Frontiers in Physics, 2021)
The Seebeck effect is investigated within the framework of a non-equilibrium Green's function technique in a quantum dot (QD) sandwiched between the left and right leads held at different temperatures. We consider that the QD is shelled by a photon field and is side-coupled to a topological superconductor nanowire hosting Majorana zero modes (MZMs). It is found that the thermopower (Seebeck coefficient) can be obviously enhanced by weak QD-MZMs coupling at low temperatures, in addition to its sign reversion that may be used for detecting the existence of MZMs. In the presence of a photon field, the thermopower can be further enhanced due to decreased electrical conductance when electrons' transport probability through each channel is reduced by photon-assisted tunneling (PAT). The hybridization between the MZMs will also induce sign reversion of the thermopower in the absence of a photon field, whereas it has less impact on the thermopower when the QD is shelled by the photon field.